2020
DOI: 10.1021/acs.jpcb.0c04553
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Fully Glycosylated Full-Length SARS-CoV-2 Spike Protein Model in a Viral Membrane

Abstract: This technical study describes all-atom modeling and simulation of a fully glycosylated full-length SARS-CoV-2 spike (S) protein in a viral membrane. First, starting from PDB: 6VSB and 6VXX, full-length S protein structures were modeled using template-based modeling, de-novo protein structure prediction, and loop modeling techniques in GALAXY modeling suite. Then, using the recently determined most occupied glycoforms, 22 N-glycans and 1 O-glycan of each monomer were modeled using Glycan Reader & Modeler in CH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
227
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(230 citation statements)
references
References 67 publications
3
227
0
Order By: Relevance
“…Even less is known at the needed molecular level about the mechanism by which the FPs in the spearhead are involved in the fusion of the cell and virus membranes, despite the wealth of information that has recently accumulated from molecular dynamics (MD) simulations on SARS-CoV-2 models (e.g., see Refs. [24][25][26][27][28][29] ).…”
Section: Introductionmentioning
confidence: 99%
“…Even less is known at the needed molecular level about the mechanism by which the FPs in the spearhead are involved in the fusion of the cell and virus membranes, despite the wealth of information that has recently accumulated from molecular dynamics (MD) simulations on SARS-CoV-2 models (e.g., see Refs. [24][25][26][27][28][29] ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies 20,21 have shown the ability of the SARS-CoV2 virus to utilize a highly glycosylated spike (S) protein to elude the host's immune system and bind to its target membrane receptor, ACE2, thus enabling entry into human cells. Based on the structural complementarity and steric impediments between the S protein and human ACE2 (hACE2) protein membranes, we mapped the glycosylation sites of both models [21][22][23][24] and performed molecular dynamics simulations (MDS) by 250 ns to stabilize the glycosylated SARS-CoV2 spike (S) and hACE2 complex (suppl .…”
Section: Resultsmentioning
confidence: 99%
“…Epitopes that coincided with previously reported epitopes or had overlapping residues, were merged into one peptide which covers all reported and predicted epitopes and are shown in bold letters in Supplementary Table 1. To visualise the position of the compiled epitopes we used an optimised 3D model of the SARS-CoV-2 spike glycoprotein as a monomer (Supplementary figure 1) and in its trimeric conformation (Figure 2) (19). B cell epitopes reported in the literature are distributed in all domains of the spike glycoprotein similarly to epitopes predicted in this study (Supplementary figure 1A & B).…”
Section: Resultsmentioning
confidence: 99%
“…To provide a graphical representation of the epitopes, we used the structural model of the full-Length SARS-CoV-2 spike glycoprotein (ID: 6VSB_1_1_1) (18, 19). The 3D structures were built and analysed using PyMOL ® software (Schrödinger LLC.…”
Section: Methodsmentioning
confidence: 99%